HPV Infection and Cervical Cancer Among Canadian Aboriginal Women - Cummings, Laura; Pickering, Christina; Sandhu, Simran; Hemet, Danielle (Université d'Ottawa | University of Ottawa, 2014)
Background: Cervical cancer is one of the most common gynecological cancers worldwide, considered to primarily result from infection with oncogenic strains of human papillomavirus (HPV) [1]. Recently, Canadian cervical cancer incidence has generally declined [2]. However, cervical cancer prevalence remains relatively high among Aboriginal women [3]. Purpose/objectives: This review aims to examine the disproportionate prevalence of cervical cancer among Canadian Aboriginal women in comparison to their non-Aboriginal counterparts, while addressing possible explanatory factors. It intends to analyze whether an association exists between HPV infection rates and higher cervical cancer prevalence. Methods: A structured literature review was conducted to compare HPV prevalence in Aboriginal and non-Aboriginal Canadian women. Peer-reviewed studies were obtained from PubMed (MEDLINE) & CINAHL (EBSCO) and assessed for quality before inclusion. Results: Although overall HPV infection prevalence remains similar between Aboriginal and non-Aboriginal women, the prevalence of high-risk HPV (HR-HPV) appears to be greater among Aboriginal women. Differential exposure to risk factors associated with HPV infection within the Aboriginal population may explain these findings. Conclusions: Differences in HPV prevalence between Aboriginal and non-Aboriginal women may explain why cervical cancer prevalence is higher among Canadian Aboriginal women. Further studies are recommended to identify underlying factors explaining these observed differences.